Implication of Profitability, Capital Structure and Liquidity to The Value of The Company - Miftakhul Ichsan Furqoni (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
Abstract— The purpose of this study was to determine the influence and formulate recommendations from the ROE, DER and CR. This research is a causal with quantitative approach. Independent variable is the profitability, capital structure and liquidity, while the dependent variable is the value of the company. Analysis of the data used is inferential statistical analysis. This study uses panel data regression analysis were processed using software eviews .From the results of the study stated that ROE, DER and CR had effected PBV simultaneous and variable of ROE has positive and significant to company value.